Political polarization - Avinash K. Dixit; Jörgen W. Weibull (Stockholm School of Economics, The Economic Research Institute (EFI), 2007)
Failures of government policies often provoke opposite reactions from citizens; some call for a reversal of the policy while others favor its continuation in stronger form. We offer an explanation of such polarization, based on a natural bimodality of preferences in political and economic contexts, and consistent with Bayesian rationality.
Keywords: D72; D74; D81; D82; 330; polarization; voting; information; Verhaltensökonomik; Beschränkte Rationalität; Politische Kultur; Staatliche Information; Theorie